2006
DOI: 10.1080/17450390600973642
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous ileal losses of nitrogen and amino acids in pigs and piglets fed graded levels of casein

Abstract: In order to determine ileal losses of nitrogen (N) and amino acids (AA) and the coefficients of apparent and true ileal digestibility (AID, TID) of N and AA from casein in piglets and pigs, two experiments were conducted. In Experiment 1, 24 piglets were used. The piglets were weaned at 17 days of age, weighing 6.4 kg and cannulated at terminal ileum. Ileal digesta was collected at 28-29 and 35-36 days of age in period 1 and 2, respectively. Feed intake was 150 and 300 g x d(-1) during the first and second per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
22
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 34 publications
13
22
0
8
Order By: Relevance
“…Our estimates of ILE N (1.38 and 0.84 g kg − 1 DM intake) at different BW were low compared with earlier reported estimates on mean flow of basal ILE N ; 1.14 g kg − 1 DM intake (Jondreville et al, 1995) and 1.89 g kg − 1 DM intake (Jansman et al, 2002). Moreover, the effect of BW on ILE N and ILE AA found in the present study agrees with previous reported values on ILE N mean flow; 2.54 and 1.43 g kg − 1 DM intake at 24 and 105 kg BW, respectively (Leterme and Théwis, 2004) and 3.44 and 2.81 g kg − 1 DM intake at 6.4 and 52.5 kg BW, respectively (Mariscal-Landín and Reis de Souza, 2006). The results from the present experiment should be interpreted with some caution because feeding levels were confounded with BW.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our estimates of ILE N (1.38 and 0.84 g kg − 1 DM intake) at different BW were low compared with earlier reported estimates on mean flow of basal ILE N ; 1.14 g kg − 1 DM intake (Jondreville et al, 1995) and 1.89 g kg − 1 DM intake (Jansman et al, 2002). Moreover, the effect of BW on ILE N and ILE AA found in the present study agrees with previous reported values on ILE N mean flow; 2.54 and 1.43 g kg − 1 DM intake at 24 and 105 kg BW, respectively (Leterme and Théwis, 2004) and 3.44 and 2.81 g kg − 1 DM intake at 6.4 and 52.5 kg BW, respectively (Mariscal-Landín and Reis de Souza, 2006). The results from the present experiment should be interpreted with some caution because feeding levels were confounded with BW.…”
Section: Discussionsupporting
confidence: 95%
“…TiO 2 was analysed according to Short et al (1996) and was used as an indigestible marker for calculations of digestibility and endogenous losses of N and AA in ileal digesta. The ILE N and ILE AA were estimated as described by Mariscal-Landín and Reis de Souza (2006). It was assumed that N and AA in the CA diet had a TID of 100% and that this diet did not induce specific ILE N and ILE AA .…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…En el periodo experimental (primer periodo) los ocho cerdos se alimentaron con una de las dos dietas experimentales (cuatro cerdos por tratamiento); en el segundo periodo (no experimental, utilizado para conocer la digestibilidad de la proteína y aminoácidos de la caseína en cada cerdo), los ocho cerdos se alimentaron con la dieta testigo (dieta a base de caseína); y su digestibilidad únicamente se utilizó para estimar la DAI de los subproductos de cártamo utilizando el método de diferencia (18) , y posteriormente se estimó la DEI según el método propuesto por Furuya y Kaji (10) empleando los valores de pérdidas endógenas reportadas por Mariscal-Landín y Reis de Souza (19) . Los datos de la DAI de las dietas experimentales (caseína-Subproductos de cártamo) y la DAI y DEI de los subproductos de cártamo se analizaron de acuerdo a un diseño completamente al azar (14) , empleando el procedimiento GLM del paquete estadístico SAS (15) ; existiendo cuatro repeticiones por dieta (tratamiento).…”
Section: Ex Perimento 2 Digestibilidad Aparente Ileal (Dai)unclassified
“…Para estimar la digestibilidad estandarizada ileal (DEI) se utilizó la fórmula propuesta por Furuya y Kaji (10) : DEI = DAI + (Endógeno Consumido) × 100 ⁄ Donde DEI es la digestibilidad estandarizada ileal de un nutrimento, DAI es la digestibilidad aparente ileal de un nutrimento, Endógeno es la cantidad endógena excretada del nutrimento en mg/kg de materia seca consumida (en el cálculo se utilizó el endógeno reportado por Mariscal-Landín y Reis de Souza (19) ), Consumido es la cantidad de nutrimento consumido en miligramos por kilo de materia seca consumida.…”
Section: Análisis De Los Datosunclassified
“…ó ⁄ Donde CDEI es el coeficiente de digestibilidad estandarizada ileal de un nutrimento, CDAI es el coeficiente de digestibilidad aparente ileal de un nutrimento, endógeno es la cantidad endógena excretada del nutrimento en mg/kg de materia seca consumida, en el cálculo se utilizó el endógeno reportado por Mariscal-Landín y Reis de Souza (16), consumido es la cantidad de nutrimento consumido en mg/kg de materia seca consumida.…”
unclassified